1975
DOI: 10.1007/bf00567111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous propranolol and metoprolol and their interaction with isoprenaline on pulmonary function, heart rate and blood pressure in asthmatics

Abstract: The effects of propranolol (0.06 mg/kg i.v.), the selective beta1-receptor antagonist metoprolol (0.12 mg/kg i.v.) and a placebo on pulmonary function, heart rate and blood pressure have been compared in asthmatics. The interaction of these drugs with increasing doses of isoprenaline on the same variables was also studied. The two beta-blockers reduced resting heart rate to the same extent, indicating the same degree of blockade of cardiac beta-receptors. Both beta-blockers reduced the basal forced expiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 18 publications
6
37
0
Order By: Relevance
“…This approach has been used in man to assess cardiac 0-adrenoceptor blockade by measuring the heart rate response to increasing doses of intravenous isoprenaline (Paterson etal, 1970;Cleaveland, Rango & Shand, 1972). A similar approach to the assessment of bronchial ,B-adrenoceptor blockade has been attempted in patients with asthma by measuring the FEV1 response to increasing intravenous doses of isoprenaline before and after P-adrenoceptor antagonists (Johnsson, Svedmyr & Thiringer, 1975;Thiringer & Svedmyr, 1976 with initial airway diameter (Benson, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been used in man to assess cardiac 0-adrenoceptor blockade by measuring the heart rate response to increasing doses of intravenous isoprenaline (Paterson etal, 1970;Cleaveland, Rango & Shand, 1972). A similar approach to the assessment of bronchial ,B-adrenoceptor blockade has been attempted in patients with asthma by measuring the FEV1 response to increasing intravenous doses of isoprenaline before and after P-adrenoceptor antagonists (Johnsson, Svedmyr & Thiringer, 1975;Thiringer & Svedmyr, 1976 with initial airway diameter (Benson, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…(Bernecker & Roetscher, 1970;Waal-Manning & Simpson, 1971;Formgren, 1972), acebutolol (Skinner & Palmer, 1974) and metoprolol (Johnsson, Svedmyr & Thiringer, 1975)], atenolol does pose a potential hazard to asthmatics. Skinner & Palmer (1974) conclude that any ,-adrenoceptor blocking drug must be used with extreme caution in asthmatics, and Johnsson et al (1975) combined with afl2-receptor-stimulating drug.…”
Section: Airways Resistancementioning
confidence: 99%
“…Kumana, Kaye, Leighton, Turner & Hamer (1975) used vigorous exercise to achieve this, and under these conditions showed no difference between propranolol and acebutolol. Johnsson et al (1975) used isoprenaline infusion and demonstrated that metoprolol permitted an excellent bronchodilator response in contrast to propranolol which almost completely blocked this effect. Similarly Skinner & Palmer (1974), using isoprenaline aerosol, demonstrated that practolol was cardioselective and acebutolol relatively less selective.…”
Section: Airways Resistancementioning
confidence: 99%
“…They Isoprenaline testing has recently been extended to include measurement of respiratory function for the assessment of cardioselectivity. Graded doses of isoprenaline by continuous intravenous infusion have been employed in asthmatic patients in whom FEV1, heart rate and blood pressure by sphygmomanometry have been recorded (Johnsson, Svedmyr & Thiringer, 1975;Thiringer & Svedmyr, 1976). In both studies metoprolol and propranolol were compared; in one of them, practolol was also included.…”
Section: Cardioselectivitymentioning
confidence: 99%